REPRESENTASI GENDER DALAM PENGGUNAAN BAHASA: ANALISIS SOSIOLINGUISTIK PADA NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER - Carly Rosyidi, Bella Nafrilia; Puspita, Ayunda Riska (Departemen Sastra Indonesia, 2024)
The purpose of the study is to identify and analyze how the use of language in the novel Gadis Pantai reflects and influences gender representation, as well as to understand how it affects the reading of gender roles and positions in society. This research method uses a qualitative descriptive research method. Qualitative descriptive research is a research method that aims to describe or explain phenomena in detail, depth, and comprehensively. In the novel